Distribution of Clostridium perfringens and Fecal Sterols in a Benthic Coastal Marine Environment Influenced by the Sewage Outfall from McMurdo Station, Antarctica - Edwards, Diane D. (American Society for Microbiology, 1998)
The spatial distribution, movement, and impact of the untreated wastewater outfall from McMurdo Station, Antarctica, were investigated under early austral summer conditions. The benthic environment was examined to determine the distribution of Clostridium perfringens in sediment cores and the intestinal contents of native invertebrates and fish along a transect of stations. These stations extended ca. 411 m south of the outfall. The findings revealed that the concentration of C. perfringens decreased with depth in the sediment and distance from the outfall. High percentages of tunicates and sea urchins were colonized with this bacterium along the transect. Coprostanol concentrations were also measured in sediment samples taken from each of the transect stations, and a similar trend was observed. These results are in agreement with the findings of previous studies performed with the water column and collectively provide evidence that the disposal of domestic wastes deserves special consideration in polar marine environments.